THE EPIC SCOWL: A NOTE ON THE METONYMIC BASIS AND CONTEXTUAL MEANING OF THE FORMULA ὑπόδρα ἰδών. (October 2022) - Horn, Fabian
Abstract : Drawing on the perspectives of cognitive linguistics and evolutionary biology, this contribution revisits the meaning of the Homeric formula ὑπόδρα ἰδών, literally 'looking from below', which is generally acknowledged as an indication of anger in epic poetry. A detailed examination of the phrase suggests that the facial expression it refers to was originally an inclination of the head while maintaining a fixed gaze ahead, resulting in a view from beneath lowered brows. It is argued that this position of the head serves as a functional preparation for a physical conflict, and consequently that the epic phrase ὑπόδρα ἰδών is not merely a metonym for anger but also a signal of the willingness to resort to violence if the conflict is not resolved by other means. This is also borne out by the contexts in which the formula occurs, since in most cases the speeches introduced with a 'look from below' are either followed by violent actions or cause their addressee to retract the offence.